AN INNOVATIVE APPROACH OF INTEGRATING SERVICE QUALITY, EMPLOYEE LOYALTY AND PROFITABILITY WITH SERVICE PROFIT CHAIN IN TELECOM SERVICE INDUSTRY: AN EMPIRICAL VALIDATION - Mohammad Sultan Ahmad Ansari (Proceedings on Engineering Sciences, 2021)
A research project was commissioned to study the influence and importance of service quality, employee loyalty, and profitability with service profit chain (SPC) model in telecom service industry in Oman. A questionnaire-based survey was conducted to investigate the consequences of a company's internal assets in terms of employees' satisfaction and loyalty, operational efficiency, and its fallout on company's turnover in terms of revenue and profitability. The telecom service chain spans three entities with service flowing from original equipment manufacturers, to telecom service providers to end users. The findings indicate that the proposed "three-tier two-stage" model holds important lessons for service industry, with service quality and human capital standing out prominently. Next, the employees' loyalty should be seen as valuable assets in an organization in order to improve company's internal performance and develop better relationships with customers and suppliers. Therefore, service quality, employee loyalty and SPC attributes should be measured periodically.